Pneumococcal vaccine effect on hospitalisation rates of pneumonia in children: A meta‐analysis. Issue 11 (24th August 2021) - Zhu, Xiuling; Li, Xiaofei
Abstract: Introduction: Since the appearance of the pneumococcal conjugate vaccine, the frequency of community‐acquired pneumonia hospitalisations was decreased significantly especially in children below the age of 2 years, but its effects are still conflicting. This meta‐analysis study was performed to assess the relationship between the effects of different types of pneumococcal conjugate vaccines compared with each other on the frequency of community‐acquired pneumonia hospitalisations in children aged below 2 years. Methods: Through a systematic literature search up to December 2020, 20 studies were found recording relationships between the effects of different types of pneumococcal conjugate vaccines compared with each other on the frequency of community‐acquired pneumonia hospitalisations in children aged below 2 years. Odds ratio (OR) with 95% confidence intervals (CIs) was calculated between different types of pneumococcal conjugate vaccines compared with each other on the frequency of community‐acquired pneumonia hospitalisations in children below the age of 2 years using the dichotomous methods with a random or fixed‐effect model. Results: The pneumococcal conjugate vaccine 10 was significantly related to a lower hospitalisation rate for pneumonia (OR, 0.64; 95% CI, 0.51‐0.81, P < .001) compared with no vaccine and (OR, 0.78; 95% CI, 0.68‐0.90, P < .001) compared with pneumococcal conjugate vaccine 7. The pneumococcal conjugate vaccine 13 was significantly related to a lower hospitalisation rate for pneumonia (OR, 0.63; 95% CI, 0.56‐0.71, P < .001) compared with no vaccine and (OR, 0.56; 95% CI, 0.36‐0.89, P = .01) compared with pneumococcal conjugate vaccine 7. The pneumococcal conjugate vaccine 13 was significantly related to a lower hospitalisation rate for pneumonia (OR, 0.67; 95% CI, 0.48‐0.93, P = .02) compared with pneumococcal conjugate vaccine 10. Conclusions: The pneumococcal conjugate vaccines 10 or 13 may have independent relationships in reducing the frequency of community‐acquired pneumonia hospitalisations in children aged below 2 years compared with no vaccine or pneumococcal conjugate vaccines 7. Also, the pneumococcal conjugate vaccine 13 may have the same independent relationship compared with pneumococcal conjugate vaccines 10. Further studies are needed to solidify the findings to other vaccines to have evidence‐based information that could help in establishing future immunisation strategies.